Mapping difference : the many faces of women in contemporary Ukraine - Rubchak, Marian J. (Berghahn Books, 2011)
Drawn from various disciplines and a broad spectrum of research interests, these essays reflect on the challenging issues confronting women in Ukraine today. The contributors are an interdisciplinary, transnational group of scholars from gender studies, feminist theory, history, anthropology, sociology, women's studies, and literature. Among the issues they address are: the impact of migration, education, early socialization of gender roles, the role of the media in perpetuating and shaping negative stereotypes, the gendered nature of language, women and the media, literature by women, and loc.